Are referrals by general practitioners influenced by the availability of consultants?. Issue 6648 (3rd September 1988) - Roland, M.; Morris, R.
Abstract : To investigate variations in the number of outpatients seen in different NHS regions of Great Britain data on numbers of outpatients, number of consultants per 100, 000 population, mortality, and prescribing rates were analysed for four specialties: medicine, thoracic medicine, psychiatry, and dermatology. The number of outpatients seen was strongly associated with the provision of consultants in all four specialties and only weakly associated with need for outpatient services as measured by standardised mortality ratios and mean numbers of prescriptions per patient issued by general practitioners. Interpretations of differences in referral rates need to take into account variations in the supply of specialists as a factor that may influence the referral behaviour of general practitioners.